Analisis Metode Pembelajaran Ceramah Masa Pandemi Covid-19 - Sukron Ma'mun (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2021)
The lecture method is one of the methods that are often used by teachers in teaching and learning activities. This method is a method that is easy to implement and also cheap, because without the media and infrastructure it can be done. Some people underestimate this method and some even argue that it is outdated and left behind. According to the author's observations, this method remains relevant in any situation and condition, especially if a teacher is someone who is proficient in communicating and understanding the psychological condition and level of ability of the students he or she faces. The point is khootibunnaasa 'alaa qodri uqulihim (speak to humans according to their level of knowledge). The writing of this article uses the library research method, namely by digging and reviewing the literature that is related to the theme of writing this article. The results of the study and the author's study related to this lecture learning method are still very relevant and effective, especially during this covid-19 pandemic. By taking into account the following points; first, a teacher understands the science of communication well, second, understands the psychological condition of the audience/students, third, is able to touch students' emotions, fourth, includes elements of humor and is good at telling stories, fifth, is able to use social media and technology well.